“Not a woman’s business”? On the problem of traditions and continuity of generations in Russian families of women scientists - N. L. Pushkareva (Шаги)
The anthropology of the academic community is an understudied topic in Soviet women’s history. This article examines it and draws on published memoirs of female contemporaries, their oral histories (recorded by the author), and periodicals. The main working hypothesis is that traditions of academic life have been preserved from generation to generation and that features have developed that have formed stable traditions and unwritten rules observed by representatives of different generations of academic workers. The author analyzes details of the lifestyle of three generations of female academics in the USSR and Russia who achieved professional recognition and had highly cited publications. The first are women born in 1917–1949; the second are children of the postwar baby boom, born in 1950–1969; the third — those born during 1970–1999. Comparison of the attitude of female scientists to their own achievements in comparison with the success of their friends who did not become scientists, the life attitudes of the daughters of contemporary female scientists with the attitudes of older generations led to the conclusion about the need to correct the hypothesis. Working with memories, analyzing subjective assessments of successes and failures one can conclude that significant transformations in the motivations of female scientists in Russia are connected with the changes in the public life of the country and in everyday life practices over the past 70 years. High motivation, focus on self-sacrifice in the name of Science among older women has been replaced by strict rationality and much less sentimentality in their daughters.